EFEKTIVITAS UNDANG-UNDANG INFORMASI DAN TRANSAKSI ELEKTRONIK DALAM MENANGGULANGI KEJAHATAN SIBER DI INDONESIA - Situngkir, Danel Aditia (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The Electronic Information and Transactions Law (UU ITE) is indeed an essential legal instrument needed to address cybercrime. However, to maximize its effectiveness, corrective measures are required, including legal revisions, strengthening of human resources, updating legal infrastructure, and long-term educational strategies involving all elements of society. In the future, the UU ITE is expected to function not merely as a punitive tool, but also as a catalyst for realizing a democratic, just, and human rights-respecting digital governance system. The ideal model of UU ITE effectiveness in combating cybercrime is not solely about legal enforcement, but more profoundly about balancing legal certainty, justice, human rights protection, and technological advancement. The state must be present not to intimidate digital citizens, but to protect them from real threats in cyberspace. Within the broader framework of national development, the existence of an ideal cyber legal model becomes a crucial foundation for achieving a sovereign, fair, and humane digital Indonesia.Keywords: UU ITE, Cybercrime, Indonesia.